Representasi Maskulinitas pada Tokoh Utama dalam Novel Cut Nyak Dien Karya Sayf Muhammad Isa - Isfiana Nursari; Nina Eka Putri; Furqan, Al; Farah Nazifa; Wardiana (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to reveal the forms of masculinity and their underlying factors as represented through the main character in the novel Cut Nyak Dien by Sayf Muhammad Isa. The research employs a descriptive qualitative approach, grounded in the masculinity theories of Bem as well as Lerner and Spanier, combined with a literary psychology perspective. The findings indicate a total of 14 data excerpts that represent five forms of masculinity: competitiveness (2 data), independence (3 data), decisiveness (3 data), self-confidence (3 data), and risk-taking (3 data). In addition, 9 data excerpts identify three causal factors of masculinity: cultural (3 data), social (3 data), and personal (3 data) influences. These findings demonstrate that masculinity is not exclusively tied to male characters but can be strongly embodied by female figures, especially within the context of struggle and local cultural values. This study is expected to enrich gender studies in literature and offer new interpretations of female roles and identity in Indonesian literary narratives.